Knowledge and practices of universal safety precautions among interns and first year resident doctors in a tertiary care hospital - Wadekar, Ashish A.; Singh, Vijaykumar S.; Chowdhury, Soujannya K.; Chape, Maheshchandra M. (International Journal Of Community Medicine And Public Health, 2021)
Background: Universal safety precautions also known as standard precautions are a set of evidence based clinical work practices published by Centers for Disease Control and Prevention (CDC) in 1996 and updated in 2007; the extension of blood and body-fluid precautions to all patients is referred to as universal precautions. Despite detail guidelines, the knowledge and understanding of universal safety precautions among health-care workers is found inadequate. Methods: This was a cross-sectional study carried out among interns and first year resident doctors in medical college attached to a tertiary care hospital. Around 200 doctors are enrolled in this study. Results: In our study, correct knowledge about hand hygiene found in interns was 84.1% and clinical residents 93.3% and this knowledge was practiced by 83.6%% interns and 84.1% clinical resident. The knowledge about the importance of wearing the gloves was 95.5% among interns and 95.4% among residents and facemask, eye wear was 78.5% among interns and 92% among residents, but in practice 78.5% interns and 71.5% residents were seen to use gloves and apron. Knowledge about needle stick injury was 95.5% among interns and 97.1% among resident doctors. The knowledge of interns was 81.25% for disposal of gloves and 70.5% for disposal of sharps whereas among resident doctors, it was 72.7% for gloves and 70.4% for sharps. Conclusions: In this study, we observed that overall knowledge regarding importance of hand washing, wearing gloves, risk of needle stick injury, disposal of biomedical waste were satisfactory. There was poor response regarding the steps of hand washing and recapping of needles.